Biventricular Assist Device Support for Intractable Arrhythmias From Histiocytoid Cardiomyopathy. Issue 11 (18th April 2022) - Magnetta, Defne A.; Reichhold, Allison; Thrush, Philip T.; Monge, Michael; Webster, Gregory; Joong, Anna
Abstract : Histiocytoid cardiomyopathy (HICMP) is a rare mitochondrial cardiomyopathy associated with recurrent life-threatening arrhythmias and variable degrees of systolic dysfunction. Successful heart transplantation for HICMP has been described, but there has been no published experience with biventricular assist device (BiVAD) support for intractable arrhythmias in HICMP. We report a 13 month old girl with left ventricular noncompaction and preserved systolic function who presented in cardiogenic shock secondary to incessant ventricular arrhythmias. After failed attempts at chemical and electrical cardioversion, she underwent BiVAD implantation as bridge to transplantation. Her BiVAD course was complicated by mechanical inflow obstruction during sinus rhythm, necessitating left-sided cannulation revision from an apical to atrial inflow cannula. This maneuver resolved the obstruction and the patient was transitioned to Berlin EXCOR (Berlin Heart Inc, The Woodlands, TX) BiVADs. On Berlin pumps, she had intermittent pauses (no fill/no eject) while in sinus rhythm, felt to be due to competition from intrinsic ejection. Despite these pauses, the patient experienced an uneventful remainder of her BiVAD course (205 days total) with minimal fibrin deposition and no device-related complications. BiVAD can support pediatric patients with hemodynamically significant arrhythmias to transplantation. Atrial cannulation strategy may be preferred in cases of preserved systolic function, ventricular noncompaction, and frequent rhythm changes.